Assessment of compressibility behaviour of organic soil improved by chemical grouting: an experimental and microstructural study - Ghareh, S.; Kazemian, Sina; Shahin, Mohamed (Techno Press, 2020)
Tropical organic soils having more than 65% of organic matters are named "peat". This soil type is extremely soft, unconsolidated, and possesses low shear strength and stiffness. Different conventional and industrial binders (e.g., lime or Portland cement) are used widely for stabilisation of organic soils. However, due to many factors affecting the behaviour of these soils (e.g., high moisture content, fewer mineral particles, and acidic media), the efficiency of the conventional binders is low and/or cost-intensive. This research investigates the impact of different constituents of cement-sodium silicate grout system on the compressibility behaviour of organic soil, including settlement and void ratio. A microstructure analysis is also carried out on treated organic soil using Scanning Electron Micrographs (SEM), Energy Dispersive X-ray spectrometer (EDX), and X-ray Diffraction (XRD). The results indicate that the settlement and void ratio of treated organic soils decrease gradually with the increase of cement and kaolinite contents, as well as sodium silicate until an optimum value of 2.5% of the wet soil weight. The microstructure analysis also demonstrates that with the increase of cement, kaolinite and sodium silicate, the void ratio and porosity of treated soil particles decrease, leading to an increase in the soil density by the hydration, pozzolanic, and polymerisation processes. This research contributes an extra useful knowledge to the stabilisation of organic soils and upgrading such problematic soils closer to the non-problematic soils for geotechnical applications such as deep mixing.